Brain-derived neurotrophic factor expression in serotonergic neurons improves stress resilience and promotes adult hippocampal neurogenesis. (October 2022) - Leschik, Julia; Gentile, Antonietta; Cicek, Cigdem; Péron, Sophie; Tevosian, Margaryta; Beer, Annika; Radyushkin, Konstantin; Bludau, Anna; Ebner, Karl; Neumann, Inga; Singewald, Nicolas; Berninger, Benedikt; et al.
Abstract: The neurotrophin brain-derived neurotrophic factor (BDNF) stimulates adult neurogenesis, but also influences structural plasticity and function of serotonergic neurons. Both, BDNF/TrkB signaling and the serotonergic system modulate behavioral responses to stress and can lead to pathological states when dysregulated. The two systems have been shown to mediate the therapeutic effect of antidepressant drugs and to regulate hippocampal neurogenesis. To elucidate the interplay of both systems at cellular and behavioral levels, we generated a transgenic mouse line that overexpresses BDNF in serotonergic neurons in an inducible manner. Besides displaying enhanced hippocampus-dependent contextual learning, transgenic mice were less affected by chronic social defeat stress (CSDS) compared to wild-type animals. In parallel, we observed enhanced serotonergic axonal sprouting in the dentate gyrus and increased neural stem/progenitor cell proliferation, which was uniformly distributed along the dorsoventral axis of the hippocampus. In the forced swim test, BDNF-overexpressing mice behaved similarly as wild-type mice treated with the antidepressant fluoxetine. Our data suggest that BDNF released from serotonergic projections exerts this effect partly by enhancing adult neurogenesis. Furthermore, independently of the genotype, enhanced neurogenesis positively correlated with the social interaction time after the CSDS, a measure for stress resilience. Highlights: New mouse model allowing cell-type specific overexpression of BDNF. BDNF overexpression in serotonergic neurons protects against chronic stress. In these mice, adult hippocampal neurogenesis is increased. Dentate gyrus axonal outgrowth of serotonergic neurons is enhanced.